ASSESSING ENVIRONMENTAL IMPACTS AND CIRCULARITY POTENTIAL IN BEEF PROCESSING USING LIFE CYCLE ASSESSMENT - Prathama, Kevin Aditya; Tama, ishardita Pambudi; Kusumaningdyah, Widha (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2025)
This study explores the environmental impact of beef processing operations in Surabaya, Indonesia, through the integration of Circular Economy (CE) principles and the Life Cycle Assessment (LCA) method. The analysis focuses on one of the largest slaughterhouses in East Java, examining four main stages: cattle reception, slaughtering, meat processing, and packaging. Using the ReCiPe 2016 Midpoint (H) method within OpenLCA software and the ELCD database, the study evaluates material and energy flows per functional unit of 1 metric ton of beef. The results reveal that the system is heavily dependent on fossil-based electricity and water resources, with significant greenhouse gas emissions, high freshwater usage, and unmanaged organic waste. The Global Warming Potential (GWP) category recorded the highest environmental impact, followed by fossil resource scarcity and terrestrial ecotoxicity. Waste management practices remain linear, with limited reuse or recycling efforts, while solid and liquid wastes are discharged without internal recovery processes. Benchmarking shows a considerable gap in sustainability performance compared to developed countries. The findings underscore the need for technological improvements, such as anaerobic digestion, renewable energy integration, and material recovery strategies. Implementing circular economy interventions would not only reduce environmental burdens but also add economic value through by-product utilization. This study offers critical insights for improving sustainability and resource efficiency in Indonesia’s beef industry by transitioning from linear to circular production models.